Effect of the Application of Learning Media Microsoft Teamms on Students' Learning Motivation in Basic Accounting - Siti Murtasiya Alwy; M. Yusuf A. Ngampo; Sahade Sahade (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research aims to determine the effect of implementing learning media microsoft teamson students' learning motivation in basic accounting subjects at SMA Negeri 12 Gowa. The variable in this research is the application of learning media microsoft teams as independent variable and learning motivation as dependent variable. The population is all students of class XII IPS SMA Negeri 12 Gowa consisting of 71 students. Sampling technique l using the technique random samplings many as 42 students. Data collection techniques used are observation, questionnaires and documentation. The data analysis technique used is descriptive percentage analysis, instrument test consisting of validity and reliability tests and hypothesis testing consisting of simple linear regression analysis, t-test and efficient coefficient of termination (R2) by using SPSS 25 for Windows.Based on the results of the data analysis that has been carried out, the model l simple linear regression equation Y = 23.753 + 0.468X is obtained, which means the application of learning media microsoft teams has a positive effect on learning motivation in which each addition is 1 value of the application of learning media microsoft teams, then the value of student motivation has increased 0.468. From the results of the analysis is the efficient coefficient of termination (R2) obtained the value of R2= 19.9% which means the application of learning mediamicrosoft teamshas a contribution to student learning motivation of 19.9 percent while the remaining 80.1 percent is influenced by other factors. While the results of the t-test analysis obtained a significant value of 0.003 <0.05, which means the application of learning mediamicrosoft teamssignificant effect on motivation to learn, thus the hypothesis is accepted.